2016
DOI: 10.1177/1043659616670713
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Supportive Care Factors Among African American Breast Cancer Survivors

Abstract: Introduction: Comprehensive breast cancer care includes not only diagnosis, staging, and treatment of cancer but also assessment and management of the physical, psychological, social, and informational needs, collectively known as supportive care. Several studies have documented the importance of addressing supportive care factors among breast cancer survivors.However, there appears to be a paucity of research concerning African American breast cancer survivors (AABCS). Therefore, the purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…In a similar study, Koçan and Gürsoy 20 reported that some breast cancer patients with mastectomy expressed that they regarded their situation as the will of God and turned to God as a source of strength and acceptance. The findings of this study are further supported by Davis et al 30 who also reported that the participants in their study indicated unequivocally that their faith in God formed the primary support for their continued survivorship.…”
Section: Religion and Faithsupporting
confidence: 86%
“…In a similar study, Koçan and Gürsoy 20 reported that some breast cancer patients with mastectomy expressed that they regarded their situation as the will of God and turned to God as a source of strength and acceptance. The findings of this study are further supported by Davis et al 30 who also reported that the participants in their study indicated unequivocally that their faith in God formed the primary support for their continued survivorship.…”
Section: Religion and Faithsupporting
confidence: 86%
“…This is an important finding given that within the African American community, African American breast cancer survivors are altruistic 27 and exude a sense of openness about their disease to family and friends. 28 Building on the strong social network, the African American church is viewed as the central community resource and the ideal setting (in collaboration with clergy) for church-based health promotion interventions to reach diverse groups. Community-based interventions had a notable impact on breast cancer screening among African American congregants.…”
Section: Discussionmentioning
confidence: 99%
“…Navodi se da lečeni od karcinoma dojke i dalje doživljavaju osećaj neizvesnosti o budućnosti, strah od ponovne pojave recidiva, simptoma, neželjenih efekata lečenja, što može komplikovati rehabilitaciju nakon lečenja i imati negativan uticaj na kvalitet života [21]. Međutim, u mnogim slučajevima nisu zadovo-ljene potrebe za podrškom [22]. Ovo je često zbog niskog prioriteta suportivne nege u zdravstvenim sistemima sa oskudnim resursima [23][24][25].…”
Section: Diskusijaunclassified